Modelo de desarrollo de las microempresas del grupo “El Salinerito” en el Ecuador - Vizueta Tomalá, Victor Hugo (2018)
Through this article, an attempt will be made to analyze the development model of the microenterprises of the "El Salinerito" Group of the Salinas de Guaranda parish in the province of Bolivar in Ecuador. The research carried out presents some elements that explain the model of microenterprise development as: the collective and solidary work of the residents of the Salinas parish, the planning of the agro-industrial production based on values such as work, cooperation, saving, self-management,reinvestment of their utilities and social entrepreneurship and the proper application of distribution channels and marketing of their products. The process of social entrepreneurship of the Salinas parish and its micro-enterprises is oriented towards theprinciples of Good Living and the reinvestment of its profits in social projects with the aim of improving the standard of living of its inhabitants.